Matching ICD‐11 personality status to clinical management in a community team—The Boston (UK) Personality Project: Study protocol. (27th April 2022) - Jha, Mithilesh; Barrett, Barbara; Brewin, Chris; Bowker, Geoff; Harwood, Nick; Jalil, Iram; Crawford, Mike; Phull, Jaspreet; Allen, Katherine; Duggan, Conor; Yang, Min; Tyrer, Peter
Abstract: Epidemiological studies show 30% to 50% of all patients in community mental health teams have personality disorders. These are normally comorbid with other psychiatric disorders, often as Galenic syndromes, and are seldom identified. In the Boston (UK) Personality Project all patients under a community health service in Boston in Lincolnshire will be asked to agree to have their personality status assessed using scales recording the new ICD‐11 classification, together with clinical ratings, social function and satisfaction. A control group of 100 patients from an adjacent service of similar demographics (Spalding) will also have similar ratings but no personality assessments. Changes in clinical status, social function and service satisfaction will be made after 6 and 12 months in both groups. The patients in the Boston group will be offered matched interventions using a stepped care approach for both the severity of disorder and its domain structure. These interventions will include shorter versions of existing psychological treatments, environmental therapies including nidotherapy, adaptive and acceptance models, drug reduction and social prescribing. Full costs of psychiatric care will be measured in both groups. The main hypothesis is that greater awareness of personality function will lead to better clinical outcomes and satisfaction.